A circular economy model of economic growth. (November 2015) - George, Donald A.R.; Lin, Brian Chi-ang; Chen, Yunmin
Abstract: The main purpose of this paper is to present a theoretical model incorporating the concept of circular economic activities. We construct a circular economy model with two types of economic resources, namely, a polluting input and a recyclable input. Overall, our results indicate that the factors affecting economic growth include the marginal product of the recyclable input, the recycling ratio, the cost of using the environmentally polluting input and the level of pollution arising from the employment of the polluting input. Our analysis also shows that, contrary to the Environmental Kuznets Curve (EKC), environmental quality cannot be maintained or improved via economic growth. Instead, the improvement in environmental quality, as measured by a reduction in pollution, can only be achieved by an increase in the environmental self-renewal rate or the recycling ratio. Highlights: A closed circular economy model is presented. Environmental quality cannot be maintained or improved via economic growth. The improvement in environmental quality can be achieved by an increase in the recycling ratio.